257 Comparing Practice Testing to Restudying in the Dissecting Room: An Experimental Study. (28th February 2022) - Elhassan, A.B.E.; Ibrahim, A.; Saad, M.; Awad, K.; Salman, M.S.T.; Mohammed, O.A.A.; Ali, M.; Bashir, S.A.T.; Mohamed, N.E.M.; Mohammed, M.A.A.
Abstract: Aim: Medical students employ many strategies for learning, most commonly restudying. However, evidence suggests that restudying is not as effective as other strategies, namely practice testing. Different studies have compared restudying to practice testing on a variety of subjects. Few studies have assessed the effect of practice testing in anatomy courses. To the best of the authors' knowledge, no studies have investigated practice testing in the dissecting room (DR). In this study, we aim to measure the effect of practice testing in a DR setting, as compared to restudying. Method: Second-year medical students learning the cardiovascular system were included in the study. Two groups were randomly selected to participate in practice tests taken at the end of DR sessions. The other two groups were asked to restudy the material. At the end of the four-week course, all students took a 15 points multiple-choice exam on learned material. Authors of practice tests were blind to the final exam content and vice versa. Results: One hundred eight students participated in the study. Fifty-three students were in the practice testing group, and 55 were in the restudying group. The practice testing group performed significantly better than the restudying group (p = .008), with a mean of 8.57 +/- 2.3 for the practice testing group and 7.27 +/- 2.6 for the restudying group. Conclusions: Practice testing significantly improved retention of Anatomy. We recommend that practice testing is implemented regularly at the end of DR sessions to enhance the learning experience.